1975
DOI: 10.1016/0031-9384(75)90189-4
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and endocrine responses of rats with hereditary hypothalamic diabetes insipidus (Brattleboro strain)

Abstract: BOHUS, B., Tj. B. VAN WIMERSMA GREIDANUS AND D. DE WIED. Behavioral and endocrine responses of rats with hereditary hypothalamic diabetes insipidus (Brattleboro strain). PHYSIOL. BEHAV. 14(5) [609][610][611][612][613][614][615] 1975. -Behavioral and endocrine profiles were established of homozygous (HO-DI) and heterozygous (HE-DI) rats with hereditary hypothalamic diabetes insipidus in comparison to Wistar strain rats. HO-DI rats were inferior m acquiring and maintaining active and passive avoidance behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1979
1979
2002
2002

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Administration of AVP induces a dose-dependent long lasting inhibition of extinction of active avoidance behavior and an improvement of passive avoidance behavior (Van Wimersma Greidanus and De Wied, 1977). Concerning endogenous AVP it has been shown that Brattleboro rats, homozygous for diabetes insipidus, which lack AVP completely, show disturbances in avoidance behavior (De Wied, Bohus, and Van Wimersma Greidanus, 1975;Bohus, Van Wimersma Greidanus, and De Wied, 1976;Bailey and Weiss, 1979) and similar phenomena are observed in Wistar rats treated intracere-broventricularly (i.c.v.) with AVP-antibodies in order to neutralize bioavailable AVP in the brain (Van Wimersma Greidanus, Dogterom, and De Wied, 1975;De Wied, 1975a, Bohus, Urban, Van Wimersma Greidanus, and.…”
Section: Introductionmentioning
confidence: 69%
“…Administration of AVP induces a dose-dependent long lasting inhibition of extinction of active avoidance behavior and an improvement of passive avoidance behavior (Van Wimersma Greidanus and De Wied, 1977). Concerning endogenous AVP it has been shown that Brattleboro rats, homozygous for diabetes insipidus, which lack AVP completely, show disturbances in avoidance behavior (De Wied, Bohus, and Van Wimersma Greidanus, 1975;Bohus, Van Wimersma Greidanus, and De Wied, 1976;Bailey and Weiss, 1979) and similar phenomena are observed in Wistar rats treated intracere-broventricularly (i.c.v.) with AVP-antibodies in order to neutralize bioavailable AVP in the brain (Van Wimersma Greidanus, Dogterom, and De Wied, 1975;De Wied, 1975a, Bohus, Urban, Van Wimersma Greidanus, and.…”
Section: Introductionmentioning
confidence: 69%
“…rats in various ways, many differences possibly associated secondarily with the loss of vasopressin. These include impaired growth (Haack, Homsy, Kohrs, Mohring, Oster & Mohring, 1975), an impaired ability to learn avoidance behaviour in response to noxious stimuli (Bohus, Van Wimersma Greidanus, & De Wied, 1975) and an impaired adrenal response to stress (McCann, Antunes-Rodriguez, Nallar & Valtin, 1966). This latter impairment may be particularly relevant since glucocorticoids appear to be necessary for the normal response to stress, such as the restitution of blood volume after haemorrhage (Gann & Pirkle, 1975).…”
Section: Resultsmentioning
confidence: 99%
“…Bohns et at. [3] and de Wied et at. [9] reported that homozygous Brattleboro rats showed faster extinction performance in shuttle box and pole jump active avoidance situations as well as decreased retention in a step-through passive avoid ance task.…”
mentioning
confidence: 99%